2022
DOI: 10.1038/s41598-022-23311-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-dependent cellular cytotoxicity-null effector developed using mammalian and plant GlycoDelete platform

Abstract: Cancer therapy using immune checkpoint inhibitor antibodies has markedly shifted the paradigm of cancer treatment. However, methods completely eliminating the effector function of these signal-regulating antibodies is urgently required. The heterogeneity of glycan chains in antibodies limits their use as therapeutic agents due to their variability; thus, the development of uniform glycan chains is necessary. Here, we subjected the anti-programmed cell death protein (PD)-1 antibody nivolumab, a representative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Expression of activation associated secretory protein 1 (ASP1) from helminth in the seeds of the GlycoDelete plant showed that the two ASP1 N ‐sites were completely trimmed to a single GlcNAc (Piron et al ., 2015 ). The GlycoDelete technology was also validated in the yeast Pichia pastoris (Wang et al ., 2020 ), the filamentous fungus Aspergillus oryzae (Li et al ., 2020 ) and CHO cells (Kang et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of activation associated secretory protein 1 (ASP1) from helminth in the seeds of the GlycoDelete plant showed that the two ASP1 N ‐sites were completely trimmed to a single GlcNAc (Piron et al ., 2015 ). The GlycoDelete technology was also validated in the yeast Pichia pastoris (Wang et al ., 2020 ), the filamentous fungus Aspergillus oryzae (Li et al ., 2020 ) and CHO cells (Kang et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%